OVERVIEW OF CLASS-I TRIPARTITE MOTIF (TRIM) PROTEINS SPECIFICALLY TRIM67 - S. N. Panhwar; C. Huang; Q. Luo; X. Yu; L. Jia; W. Liu; Z. Chen (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences)
The TRIM family is a group of genes expressed during embryogenesis. This review emphasized data on Class-I TRIM genes, including TRIM1, TRIM9, TRIM36, TRIM46, TRIM67, TRIM18, and TRIM76. This article will discuss the structure and function of these genes and their roles in various physiological processes such as embryonic development, and immune regulation.  Class-I TRIM proteins develop as E3 ubiquitin ligases and work with E2 ubiquitin-conjugating enzymes.  TRIM9 is expressed in the stem cells of mice and linked to various neuronal functions and neurological diseases. TRIM18 is found in microtubules and cellular filaments. TRIM36 is associated with neuro-pathological mutations, while TRIM46 controls microtubule organisation during axon formation. TRIM67 plays a significant role in neuritis outgrowth, lipid phosphate phosphatase, and colorectal and lung carcinomas. It also involves cell proliferation and induces morphological changes like neuronal differentiation. TRIM67 is important in Plasticity-related gene-1 (PRG-1). Deletion of prog-1 in mice results in epileptic seizures, indicating the significance of TRIM67 in brain development and growth. TRIM76 is associated with cardiac diseases. Further identification and characterisation of novel TRIM members will provide new insights into the functions of these essential proteins in health and disease.